Maximizing Learning Outcomes through Printed and Digital Learning Materials among Junior High School Students - Delona Ria Polhaupessy; Rosina FJ Lekawael; Inggrit Tanasale (ITScience (Information Technology and Science), 2026)
This study aims to analyze junior high school students' perceptions of the pedagogical superiority of printed and digital learning materials within a blended learning framework. The study used a quantitative descriptive survey design involving 30 students as respondents. Data were collected through a structured questionnaire that measured usage patterns, learning needs, and each medium's contribution to the learning process. The results showed that both types of media were perceived positively, but had different and complementary pedagogical functions. Print media was preferred to support concentration and intensive reading (Mean = 4.12), indicating its role in maintaining cognitive stability, strengthening conceptual understanding, and supporting in-depth reading. In contrast, digital media received a higher average score (Mean = 4.25) for motivation and learning engagement, attributable to interactivity, multimodality, and immediate feedback features. However, the effectiveness of digital media was moderated by structural factors, with 30% of respondents reporting connectivity constraints and device limitations as significant barriers. Another important finding was that 90% of students recommended the hybrid approach, indicating metacognitive awareness of diverse learning needs. Thus, this study concludes that modernizing junior high school learning is not effective when achieved through full digitization, but rather through adaptive instructional design that integrates the tactile consistency and conceptual depth of print media with the flexibility and interactivity of digital media, in a contextually and equitably integrated manner.